The Islamic Social Reporting Index and Investment Account Holder in Islamic Banks - Nadia Putri; Sepky Mardian (IAIN Salatiga, 2020)
This research aims to discover the influence of Corporate Social Responsibility (CSR) disclosure based on the Islamic Social Reporting (ISR) index towards Investment Account Holder (IAH) in 11 Islamic banks in Indonesia from 2013-2018. The dependent and independent variables comprise the growth of temporary Syirkah funds representing IAH and prior studies. This is an associative research with secondary data obtained from the annual report. Panel data regression was used as the analysis technique with Fixed Effect Model (FEM) chosen as the best estimation model. The result showed that the ISR index towards IAH negatively influences CSR disclosure. Furthermore, the dominant floating market customers in Indonesia tend to force Islamic banks to focus on reporting related returns, sharia-compliant transactions, and excellent service to customers rather than disclosing social factors. This trend also exists in Islamic banks in several countries, besides the absence of regulations and guidelines for social reporting standards. The social reporting guidelines issued by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) are only voluntary to be implemented by Islamic banks